2013
DOI: 10.4236/abb.2013.45088
|View full text |Cite
|
Sign up to set email alerts
|

Bioremediation of malathion in soil by mixed Bacillus culture

Abstract: Degradation of a pesticide, malathion, in soil by Bacillus sp has been reported during current study. A simple and highly sensitive reverse phase HPLC-UV (High pressure liquid chromatography-Ultraviolet) method was used for determination of malathion degradation in soil. The bioremediation of was performed in malathion contaminated sterile and nonsterile soil and it was found that 84.81% and 74.11% of malaoxon, respectively, from malathion concentration of 1.5% kg −1 soil was degraded by strain PU after 7 days… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 10 publications
2
8
0
Order By: Relevance
“…These results agree [4,5], which reported the derivative ability of cyanobacterial mats for Acetochlor and Diuron. Further support to our results is in Singh et al [29] report that stated higher levels of Malathion degradation in soil due to a mixed culture of three bacterial strains. In contrast, Ibrahim et al [30] investigated the growth of three strains of filamentous cyanobacteria under different concentrations of Malathion and found a sharp decrease in the growth of filamentous cyanobacterial by increasing the concentration of Malathion.…”
Section: Effects On Population Growthsupporting
confidence: 92%
“…These results agree [4,5], which reported the derivative ability of cyanobacterial mats for Acetochlor and Diuron. Further support to our results is in Singh et al [29] report that stated higher levels of Malathion degradation in soil due to a mixed culture of three bacterial strains. In contrast, Ibrahim et al [30] investigated the growth of three strains of filamentous cyanobacteria under different concentrations of Malathion and found a sharp decrease in the growth of filamentous cyanobacterial by increasing the concentration of Malathion.…”
Section: Effects On Population Growthsupporting
confidence: 92%
“…Janeczko et al (2014) demonstrated that activated sludge can degrade malathion in laboratory-scale bioreactors. There is also circumstantial evidence showing that isolates common to activated sludge can biodegrade malathion (Singh et al, 2013). These findings stand in contrast to the results of Tsezo and Bell (1991), who used radiolabeling to demonstrate that sorption and abiotic degradation, not microbial activity, were primarily responsible for malathion removal in activated sludge.…”
Section: Introductionmentioning
confidence: 65%
“…has also been reported. Residual malathion was monitored by HPLC analysis and it was found that 74.11% of malaoxon (an analog of malathion) was degraded by the strain (Singh et al, 2013). Similarly, Singh et al (2012) reported the degradation of malathion by Brevibacillus sp.…”
Section: Discussionmentioning
confidence: 99%